Investigating the reliability of using smartphone app and smartphone sensors in undergraduate laboratory experiments - Indira Dey; Santanu Choudhury (Utilitas Mathematica, 2025)
In the present work we investigated a simple and interesting experiment in physics- Dopler effect- using smartphones to study the reliability of using the smartphone app ‘Phyphox’ as a laboratory tool to perform various experiments in Physics. Doppler effect is a fundamental principle in wave mechanics with numerous applications in various scientific fields. While our experiment modelled Doppler redshift with sound, it helps us visualize why astronomers observe redshifted light from galaxies. Though cosmological redshift and Doppler shift differ in their underlying physics, the understanding of Doppler shift plays a very significant role in the development and understanding of cosmological red shift, that is a key piece of observational evidence supporting the Big Bang theory. In our experimental setup, two smartphones and a laptop are taken to study the Doppler effect. One of the smartphones is mounted on a stand which acts as a stationary source of monochromatic sound and the other, with the app ‘Phyphox’ installed acts as a moving observer. A laptop is connected to the second phone to record the frequency change as the observer moves. The experimental results of observed Doppler effect are quantitatively compared with the theoretical predictions. The agreement of experimental data with the theoretical data indicates that the method adopted is valid and the app used is reliable.